Implementation and Optimization of A Fast Inter Prediction Algorithm - Xiaoyu Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Audio Video coding Standard is the second generation Source Coding-Decoding standards of China, especially for embedded audio/video platform. This paper proposes an efficient and fast inter prediction algorithm, which is one of the key techniques of Audio Video coding Standard.Reducing of the redundancy in source sequence inter prediction, it could improve the picture quality. The optimization schemes include two aspects,which are the algorithm framework, variables and data structure. Optimized results demonstrate that our algorithm has a notable improvement of the clockcycle efficiency. Furthermore, this research also gives a valuable insight of the combination with quantum information. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.2992